Genetic studies on growth and production traits in German Angora Rabbits under sub-temperate climatic conditions - RAHIM, ABDUL; RAJARAVINDRA, K S; CHATURVEDI, OM HARI; CHAUDHARY, RAJNI; SHARMA, S R (The Indian Journal of Animal Sciences, 2022)
This study aimed to assess the effect of genetic and non-genetic factors on growth, wool yield and wool characteristics of German Angora rabbit. Data was collected on 607 adult rabbits over a period of four years (2018-2021). The least squares means of body weights (g) at various ages, wool yield (g) at I, II, III and IV clip and wool characteristics assessed by staple length (cm) and fiber diameter (μ) were estimated. Sires of the rabbit progenies demonstrated highly significant effect (P